2022
DOI: 10.3390/nu14020336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat-Treated Garlic (Allium sativum L.) on Growth Parameters, Plasma Lipid Profile and Histological Changes in the Ileum of Atherogenic Rats

Abstract: Dietary supplementation with raw garlic has a preventive and healing effect in cardiovascular diseases, but it could also damage the intestinal mucosa, resulting in impairment of nutrient absorption. Garlic processing, including heat treatment, changes the content and biological activity of garlic, so it is crucial to find food-processing methods that will preserve the health-promoting properties of garlic while minimizing its negative impact on the digestive system. Therefore, in this study, the effect of gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Additionally, with the loss of alliinase activity, the vasorelaxant properties of Allium sativum, were abolished in aortic rings pre-contracted with phenylephrine [ 95 ]. Similar dependency on alliinase activity was reported for the hypolipidemic activity of A. sativum where long heating times or microwave heating compromised this effect [ 135 ].…”
Section: Importance Of Allioideae Species In Cardiovascular Diseasessupporting
confidence: 72%
“…Additionally, with the loss of alliinase activity, the vasorelaxant properties of Allium sativum, were abolished in aortic rings pre-contracted with phenylephrine [ 95 ]. Similar dependency on alliinase activity was reported for the hypolipidemic activity of A. sativum where long heating times or microwave heating compromised this effect [ 135 ].…”
Section: Importance Of Allioideae Species In Cardiovascular Diseasessupporting
confidence: 72%
“…Many authors [11,20], as well as our study, testify to the heterogeneity not only of the intestinal wall, but also of some areas within one section of the small intestine. During histological, cytometric and ultramicroscopic studies, discrepancies in indicators were established, which indicates a deeper damage to the wall of the small intestine at the cellular level.…”
Section: Discussionsupporting
confidence: 53%
“…It has also been shown that the flavonoid and antioxidant compounds in plants have a significant effect on preventing the occurrence of hyperlipidemia and hypercholesterolemia. These compounds play an active role by influencing the expression of factors involved in this process or increasing or decreasing the activity of enzymes that affect the metabolism of these compounds (22).…”
Section: Discussionmentioning
confidence: 99%